2011
DOI: 10.1007/s12043-011-0094-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of various parameters used in proximity potential in heavy-ion fusion reactions: New extension

Abstract: An attempt has been made to modify the original proximity potential using up-to-date knowledge of the universal function and surface energy coefficient available in the literature. A new radius formula has also been obtained using the recent data on charge distribution. The detailed investigation of over 395 reactions reveal that the new proximity potential reproduces the experimental data better than earlier versions.Keywords. Nuclear reaction models and methods; fusion and fusion-fission reactions; fusion re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Recent research has shown that the Geiger-Nuttall law can be used to describe the proton radioactivity isotopes with same angular momentum [16]. In order to test our predictions, we plot the linear relationships between log 10 T Guo2013 1/2 and Q −1/2 p of proton emitters 144, 45,147 Tm, 146 Tm n , 159,160,161 Re and 164,165,166,167,169 Ir m in Fig. 5.…”
Section: The Proximity Potential Guo2013mentioning
confidence: 97%
See 1 more Smart Citation
“…Recent research has shown that the Geiger-Nuttall law can be used to describe the proton radioactivity isotopes with same angular momentum [16]. In order to test our predictions, we plot the linear relationships between log 10 T Guo2013 1/2 and Q −1/2 p of proton emitters 144, 45,147 Tm, 146 Tm n , 159,160,161 Re and 164,165,166,167,169 Ir m in Fig. 5.…”
Section: The Proximity Potential Guo2013mentioning
confidence: 97%
“…In order to overcome the shortcomings of the original version of the proximity potential (Prox.1977) [23], various improvements and modifications have been proposed. Those developments included either a better form of the surface energy coefficients [26][27][28][29][30][31][32][33], or introduced an improved universal function or another nuclear radius parameterization [24,25,[34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…00DP [18], Prox. 2010 [19] and Dutt 2011 [20]), (iv) Bass family (included Bass 73 [4] and its modified forms Bass 77 [21] and Bass 80 [22]), (v) Winther family (included CW 76 [5] and its modified forms BW 91 [23] and AW 95 [24]), (vi) Ngô 80 [6], (vii) Denisov family (included Denisov [7] and its modified form Denisov DP [18]) and (viii) Guo 2013 [8].…”
Section: The Dimensionless Universal Function  mentioning
confidence: 99%
“…Modifications to parameters in the original proximity potential have been made over time to generalize this model to fusion reactions and to overcome its shortcomings; these include the surface energy coefficient, surface thickness parameter, nuclei radius, and the universal function. Various versions of the original model now exist [2][3][4][5][6][7][8], although in some cases the modifications are minor [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation